Analisis Efektivitas Hukum Dalam Kebijakan Pengawasan Di Bidang Kepabeanan Dan Cukai Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean C Jayapura - Edy Susanto; Ramlani Lina Sinaulan; Khalimi Khalimi (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Based on the Law Number 17 of 2006 concerning Amendments to the Law Number 10 of 1995 concerning Customs, the implementation of customs and excise taxation activities adheres to a self-assessment system. Thus, there is a need for a balance related to the supervision of the implementation of the law. The supervision referred to is all supervisory activities in the customs and excise sector as regulated in the Regulation of the General Directorate of Customs and Excise Number P-17/BC/2020 concerning Procedures for Supervision in the Customs and Excise Sector. The objective of this study was to find out and analyze the implementation of supervision based on the Regulation of the General Director of Customs and Excise Number P-17/BC/2020 and the effectiveness of the law in implementing this policy at the Customs and Excise Service Office of Customs and Excise of the Middle Type C Customs Jayapura from 2020 to 2022. The method applied in this research was normative-empirical law with a statute approach and a case approach. The techniques used for collecting legal materials were a bibliography study, a document study, and a file or record study. Then, the technique of analyzing legal materials utilizing the interpretation of legal materials that had been processed. The results of the study showed that the implementation of customs and excise supervision has been following with the Regulation of the General Director of Customs and Excise Number P-17/BC/2020 with KPI achievement results ranging from 75% to 100% of the targets set from 2020 to 2022. Then, the legal effectiveness in supervision in the sector of customs and excise at the Customs and Excise Service Office of Customs and Excise of the Middle Type C Customs Jayapura from 2020 to 2022, being reviewed from the five indicators, was still not optimal, because there were still several obstacles in each of these indicators..